2012
DOI: 10.1177/0333102412463494
|View full text |Cite
|
Sign up to set email alerts
|

CACNA1H antibodies associated with headache with neurological deficits and cerebrospinal fluid lymphocytosis (HaNDL)

Abstract: Our results support the notion that ion channel autoimmunity might at least partially contribute to HaNDL pathogenesis and occurrence of neurological symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 11 publications
2
25
0
4
Order By: Relevance
“…Some patients report a preceding non-specific viral prodromal illness [6,14], but studies have failed to provide a definite viral association [2,3]. The presence of antibodies directed against the CACNA1H subunit of the T-type voltage-gated calcium channel in one small study supported the inflammatory or autoimmune hypothesis [15]. Cortical spreading depression-associated cerebral oligaemia has been observed during HaNDL attack, and may play a significant role [8,16].…”
Section: Discussionmentioning
confidence: 98%
“…Some patients report a preceding non-specific viral prodromal illness [6,14], but studies have failed to provide a definite viral association [2,3]. The presence of antibodies directed against the CACNA1H subunit of the T-type voltage-gated calcium channel in one small study supported the inflammatory or autoimmune hypothesis [15]. Cortical spreading depression-associated cerebral oligaemia has been observed during HaNDL attack, and may play a significant role [8,16].…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, a recent study has demonstrated autoantibodies to subunit of the T-type voltage-gated calcium channel, CACNA1H, has been linked to HaNDL syndrome (8). In addition, mitogen activated protein kinase-4 (MAPK-4) and DNA-dependent protein kinase catalytic subunit (DPKCU) antibodies were also detected in minority of HaNDL patients (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…[22] Kürtüncü ve ark.nın 2012 yılında yaptığı bir çalışma ile HaNDL sendromlu iki hastada T-tipi kal-PAIN A RI siyum kanal alt birimlerinden CACNA1H proteinine karşı yüksek titrede antikorlar saptanmış, iyon kanalı otoimmünitesinin sendromun patogenezine kısmen de olsa katkı sağlayabileceği görüşü desteklenmiştir. [23] HaNDL sendromunun patogenezi halen bilinmediğinden bu alanda çalışmalara gerek vardır ve ayrın-tılı olgu bildirimleri de değerlidir.…”
Section: Discussionunclassified